1998
DOI: 10.1116/1.590459
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and optical characteristics of etch induced damage in InGaAs

Abstract: Articles you may be interested inEffects of rapid thermal annealing on the optical properties of In 0.53 Ga 0.47 As/In 0.52 Al 0.48 As multiple quantum wells with InGaAs and dielectric capping layers Cl 2 plasma passivation of etch induced damage in GaAs and InGaAs with an inductively coupled plasma sourceThe effects of etch induced damage on the electrical and optical properties of AlGaAs/InGaAs quantum wells ͑QWs͒ were studied. From the variations in the photoluminescence ͑PL͒ intensity and the conductivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…For example, in the fabrication of multichip optoelectronic module ͑MOM͒ structures, the surface roughness plays a significant role since the level of scattering and microwave losses, which are related to the surface roughness, modify the optical and microwave properties of the structure. As reported by Berg and Pang, 10 the surface damage, reflectivity, sidewall damage, defect density, thermal load etc. that occur during the etching process can degrade device characteristics.…”
Section: B Surface Roughnessmentioning
confidence: 68%
“…For example, in the fabrication of multichip optoelectronic module ͑MOM͒ structures, the surface roughness plays a significant role since the level of scattering and microwave losses, which are related to the surface roughness, modify the optical and microwave properties of the structure. As reported by Berg and Pang, 10 the surface damage, reflectivity, sidewall damage, defect density, thermal load etc. that occur during the etching process can degrade device characteristics.…”
Section: B Surface Roughnessmentioning
confidence: 68%
“…E.W Berg and S.W. Pang also used conductance measurements to evaluate lateral etch damage in the GaAs material system [3]. These studies showed AlInAs/InGaAs was more susceptible to sidewall damage than the AlGaAs/InGaAs with respective dead layers of 243 nm and 146 nm.…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, an optimal rf power of 120 W was used to balance the undercut and etching selectivity. The anisotropy of dry etching greatly depended on ICP chamber pressure; 16,17 thus, 1.7 mTorr was used for chamber pressure to optimize etching anisotropy after calibration tests. The byproduct of chlorine-based InP ICP etching was InCl x , which was generally involatile below 150°C.…”
Section: Methodsmentioning
confidence: 99%